Can intra-operative intraperitoneal free cancer cell detection techniques identify patients at higher recurrence risk following curative colorectal cancer resection: a meta-analysis - Rekhraj, Sushil; Aziz, Omer; Prabhudesai, Shirish; Zacharakis, Emmanouil; Mohr, Franziska; Athanasiou, Thanos; Darzi, Ara; Ziprin, Paul (Annals of surgical oncology, 2008)
Background Accurate staging of colorectal cancer is important for predicting prognosis and guiding treatment. This study uses meta-analysis to investigate if the pre- or post-resection detection of intraperitoneal free cancer cells can predict recurrence in patients undergoing curative colorectal cancer surgery. Methods A literature search was performed on all studies between January 1990 and July 2007 comparing the detection of intraperitoneal free cancer cells either pre- or post-resection with prognosis in colorectal cancer. The following prognostic outcomes were meta-analyzed: overall recurrence rate and local recurrence rate. A random-effect model was used and heterogeneity was assessed. Results Nine studies reporting on a total of 1182 subjects matched the selection criteria. Free cancer cells were detected prior to tumor resection in 125/822 (15.2%) of patients and following resection in 64/533 (12%) of patients. Preresection, the absence of tumor cells was associated with a lower overall recurrence (25.2%) compared to the presence of tumor cells [46.4%, odds ratio (OR) = 0.41, confidence interval (CI) 0.19–0.88]; as well as a significantly lower local recurrence (12.2% versus 21.1%, OR = 0.42, CI 0.21–0.82). Postresection, the absence of tumor cells also resulted in significantly lower overall recurrence (17.3%) when compared to the presence of tumor cells (52.6%, OR = 0.07, CI 0.03–0.18). Conclusions The detection of intraperitoneal free cancer cells is associated with higher recurrence and poorer prognosis. Use of these techniques can identify patients at higher recurrence risk. This could be particularly valuable in stage II disease to identify patients who may benefit from adjuvant chemotherapy.